Clinical and laboratory characterization of adult T-cell leukemia/lymphoma in patients from Salvador, Bahia - Bomfim, Evelyn Keila dos Santos; Santos, Mariane Melo dos; Freire, Songeli Menezes; Meyer, Roberto José; Torres, Alex José Leite (Brazilian Journal of Oncology, 2021)
ATLL is a malignant and aggressive leukemia whose survival time is limited. It is known that 5% of individuals infected with HTLV-1, after many years of latency, may develop this disease. The mechanisms by which the evolution of clinical conditions occurs are unknown, and in Brazil there are few studies about ATLL, this some important themes will be addressed in this study. Thus, the objective of this study is to characterize the epidemiological and immunophenotypic profile of patients diagnosed with ATLL, attended at an oncohematological reference center in Salvador, Bahia, in the period between 2010-2018. The methodology consisted of a descriptive, retrospective of time series study, which cases of ATLL were collected from reports belonging a reference laboratory and of medical reports available from Com-HUPES. These data were treated and analyzed statistically, being observed that the majority of cases were female and that a large part have the most aggressive clinical condition Although the literature reports that ATLL clinical condition are always considered as severe, in this study it was observed that patients can achieve long survival in good clinical conditions, according to the treatment administered. In view of the available results, it is possible to conclude that exist a broad distinction between the clinical and molecular forms, being may be an important indicator of the evolution of ATLL.
Keywords: Adult T-cell leukemia-lymphoma; HTLV-1; Immunophenotyping; treatment; survival